ANALISIS PERAN TEORI AKUNTANSI TERHADAP PELAPORAN KEUANGAN DI ERA DIGITAL PADA PT PANCA ANUGERAH WISESA Tbk - Melvina Anggika Tama; Riska Dwi Amalia; Zimq Marquiza; Fifi Aprilia Yulianti; Gunawan Aji (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
Theory is a set of hypothetical, conceptual, and pragmatic principles that are interrelated with each other, and form the frame of reference of a field of knowledge. With each other, and form the frame of reference of a field of science. Accounting theory is defined as a logical thought in the form of a set of principles that is a frame of reference for evaluating accounting practices and guidelines for developing accounting practices. Frame of reference for evaluating accounting practices and guidelines for developing new practices and procedures. In the beginning accounting consisted only of very simple bookkeeping. It was only used to record economic transactions that occurred in the society at the time that time. In addition to the development of the times and human needs in all transactions, it is necessary to have basic rules that are clear and can adapt to the development of technological progress. For this reason, accounting theory is needed to answer all kinds of hypotheses about phenomena that occur in society. In society. Thinkers and researchers in the field of accounting continue to work using various methods and approaches to apply accounting theory that can be accepted by all accounting users in the world Keywords: Accounting Theory, The Role of Accounting Theory.